13C- and 15N‑Isotope Analysis of Desphenylchloridazon by Liquid Chromatography−Isotope-Ratio Mass Spectrometry and Derivatization Gas Chromatography−Isotope-Ratio Mass Spectrometry - Melsbach, Aileen; Ponsin, Violaine; Lihl, Christina; Torrento Aguerri, Clara; Hofstetter, Thomas B.; Hunkeler, Daniel; Elsener, Martin (My University, 2019)
The widespread application of herbicides impacts surface water and groundwater. Metabolites (e.g., desphenylchloridazon from chloridazon) may be persistent and even more polar than the parent herbicide, which increases the risk of groundwater contamination. When parent herbicides are still applied, metabolites are constantly formed and may also be degraded. Evaluating their degradation on the basis of concentration measurements is, therefore, difficult. This study presents compound-specific stableisotope analysis (CSIA) of nitrogen- and carbon-isotope ratios at natural abundances as an alternative analytical approach to track the origin, formation, and degradation of desphenylchloridazon (DPC), the major degradation product of the herbicide chloridazon. Methods were developed and validated for carbon- and nitrogen-isotope analysis (δ13C and δ15N) of DPC by liquid chromatography−isotope-ratio mass spectrometry (LC-IRMS) and derivatization gas chromatography−IRMS (GC-IRMS), respectively. Injecting standards directly onto an Atlantis LC-column resulted in reproducible δ13C-isotope analysis (standard deviation <0.5‰) by LC-IRMS with a limit of precise analysis of 996 ng of DPC on-column. Accurate and reproducible δ15N analysis with a standard deviation of <0.4‰ was achieved by GC-IRMS after derivatization of >100 ng of DPC with 160-fold excess of (trimethylsilyl)diazomethane. Application of the method to environmental-seepage water indicated that newly formed DPC could be distinguished from “old” DPC by the different isotopic signatures of the two DPC sources.